Case Report: A Patient With COVID-19 Who Benefited From Hemoadsorption - Du, Yinke; Qi, Zhipeng; Ma, Jiangwei; Sun, Da; Yao, Li; Xu, Bin; Liu, Wei; Xu, Zhaofa; Deng, Yu (Frontiers in Medicine, 2020)
In December 2019, the 2019 novel coronavirus disease (COVID-19), which has been identified to be caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in China and spread across the world. Higher plasma levels of cytokines, including interleukin (IL)-6, IL-2, IL-7, IL-10, and tumor necrosis factor-α, were found in patients with COVID-19, which implies the occurrence of a cytokine storm and its association with disease severity. Extracorporeal blood purification has been proven to effectively remove the released inflammatory cytokines. In this study, we report on a patient with COVID-19 who benefited from hemoadsorption operation.